PENGARUH SISTEM INFORMASI MANAJEMEN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. PLN (PERSERO) DISTRIBUSI JAKARTA RAYA DAN TANGERANG BIDANG SUMBER DAYA MANUSIA DAN KEUANGAN - Wiranda, Fahry Akbar; Prihatini, Apriatni Endang; Hidayat, Wahyu (Jurnal Ilmu Administrasi Bisnis, 2015)
Management information system and work environment are the keys to achieve employee performance. PT. PLN (Persero) Distribution Jakarta Raya and Tangerang is a company which known as supplier and electric distributor which always try to give the best service for customer. Therefore it needs human resource which have a good performance. To raise employee performance, the company should increase management information system and work environment.This type of research is using explanatory research with 72 employees at PT. PLN (Persero) Distribution Jakarta Raya and Tangerang on Human Resource Department and Finance Department as population, and altogether become the sample of this research by using census sampling. This data is collected by questionnaire, and the measurement scale is Likert. Corelation, simple linear regression and multiple linear regression is used for the analysis with SPSS Program 18.0.The results show that management information system and work environment have partial and simultaneous effect to employee performance. Management information system variable has greater effect than work environment.The suggestions to PT. PLN (Persero) Distribution Jakarta Raya and Tangerang are more often to hold coaching for entire employees in order to make management information system can be used maximally and to reduce mistakes within task completion, provide more medicines to anticipate work accident and hopefully manager could listen and take advice from employees.